2019
DOI: 10.1002/cpdd.764
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Anti–Stress Response Effects of Oxycodone Versus Sufentanil for Patients Undergoing Cardiac Valve Replacement—A Randomized Controlled Trial

Abstract: Patients undergoing cardiac valve replacement may experience cardiovascular adverse events during the preoperative period before anesthesia. The study was to compare the preemptive anti–stress response effects of oxycodone versus sufentanil for patients undergoing cardiac valve replacement. Ninety‐four patients were enrolled and assigned to group Oxy, group Suf and group NS. Patients in group Oxy were administrated with oxycodone 0.1 mg/kg, group Suf received sufentanil 0.1 μg/kg and group NS were given equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Administration of local anesthetics can reduce gastrointestinal motility, thereby reducing the risk of PONV. [62][63][64] However, this study found that there was no significant difference between bupivacaine and oxycodone on cortisol levels. In other hand, bupivacaine and oxycodone are equally effective.…”
contrasting
confidence: 54%
“…Administration of local anesthetics can reduce gastrointestinal motility, thereby reducing the risk of PONV. [62][63][64] However, this study found that there was no significant difference between bupivacaine and oxycodone on cortisol levels. In other hand, bupivacaine and oxycodone are equally effective.…”
contrasting
confidence: 54%
“…External stimuli can excite the body’s sympathetic nerves, causing the secretion of catecholamines in the body, resulting in increases in plasma dopamine, epinephrine, and norepinephrine [ 22 , 23 ]. We found that during LMA insertion, norepinephrine was significantly increased in group B.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol secretion is one of the main features of the neuroendoctrinal metabolic response to surgery. [5][6][7] Surgical stimuli in the form of a pain response and tissue trauma will activate the central nervous system and generate a stress response through two pathways known as the "hypothalamic-pituitary and sympathetic-adrenal" axes. Preemptive analgesic oxycodone can reduce cortisol secretion.…”
Section: Discussionmentioning
confidence: 99%